ZIARAH TOURISM AT THE SITE OF HABIB MUDA SEUNAGAN'S DECENDANTS' TOMB - Husaini Husda (Indonesian Journal of Islamic History and Culture, 2021)
Located in the most western part of the archipelago of Indonesia, Aceh is an area that has advantages in tourism, especially historical and religious tourism which need to be further promoted in accordance with the direction of the UUPA. Currently, Aceh has no less than 808 tourism sites that are quite interesting to be promoted, both natural objects (426), cultural objects (268) and objects of special interest (1140) scattered in 23 districts/cities. As a special area for the implementation of Sharia Law, Aceh tourism is in accordance with the flow of Islamic history and culture. One of the objects that is quite interesting and unique is the Tradition of Pilgrimage Tourism at the Tomb of Habib Muda Seunagan Descendants in Nagan Raya Regency. This paper is to examine the motivation behind a unique pilgrimage tourism tradition; How are the implementation and activities carried out by pilgrimage tours in these tombs and what uniqueness is this site possess that is different from pilgrimage traditions in other tombs in Aceh, even in Indonesia. To answer these questions, a qualitative approach with naturalistic method is used. The results of the research find a number of advantages from the excess of attitudes, behaviour and character as well as the role of the descendants of Habib Muda Seunagan, so that pilgrim tourists do activities such as suluk, fasting for 40 days, zikir ratep duablah, doing khalwat and the existence of tawaf, prayer Eid al-Adha a day earlier and other activities.